Functional interrogation of Lynch syndrome‐associated MSH2 missense variants via CRISPR‐Cas9 gene editing in human embryonic stem cells. Issue 11 (17th August 2019) - Rath, Abhijit; Mishra, Akriti; Ferreira, Victoria Duque; Hu, Chaoran; Omerza, Gregory; Kelly, Kevin; Hesse, Andrew; Reddi, Honey V.; Grady, James P.; Heinen, Christopher D.
Abstract: Lynch syndrome (LS) predisposes patients to cancer and is caused by germline mutations in the DNA mismatch repair (MMR) genes. Identifying the deleterious mutation, such as a frameshift or nonsense mutation, is important for confirming an LS diagnosis. However, discovery of a missense variant is often inconclusive. The effects of these variants of uncertain significance (VUS) on disease pathogenesis are unclear, though understanding their impact on protein function can help determine their significance. Laboratory functional studies performed to date have been limited by their artificial nature. We report here an in‐cellulo functional assay in which we engineered site‐specific MSH2 VUS using clustered regularly interspaced short palindromic repeats‐Cas9 gene editing in human embryonic stem cells. This approach introduces the variant into the endogenous MSH2 loci, while simultaneously eliminating the wild‐type gene. We characterized the impact of the variants on cellular MMR functions including DNA damage response signaling and the repair of DNA microsatellites. We classified the MMR functional capability of eight of 10 VUS providing valuable information for determining their likelihood of being bona fide pathogenic LS variants. This human cell‐based assay system for functional testing of MMR gene VUS will facilitate the identification of high‐risk LS patients.